Construction and analysis of gene co-expression network in the pathogenic fungus Ustilago maydis - Soberanes-Gutiérrez, Cinthia V.; Castillo-Jiménez, Alfredo; Pérez-Rueda, Ernesto; Galán-Vásquez, Edgardo (Frontiers in Microbiology, 2022)
Biological systems respond to environmental disturbances and a wide range of compounds through complex gene interaction networks. The enormous growth of experimental information obtained using large-scale genomic techniques such as microarrays and RNA sequencing led to the construction of a wide variety of gene co-expression networks in recent years. These networks allow the discovery of clusters of co-expressed genes that potentially work in the same process linking them to biological processes often of interest to industrial, medicinal, and academic research. In this study, we built the genetic co-expression network of Ustilago maydis from the gene expression data of 168 samples belonging to 19 series, which correspond to the GPL3681 platform deposited in the NCBI. This network was analyzed to identify clusters of co-expressed genes, gene hubs and Gene Ontology terms. Finally, we identified relevant modules through a hypergeometric approach based on a predicted set of transcription factors and virulence genes.